Effect of bovine cumulus–oocyte complexes‐conditioned medium on in‐vitro maturation of canine oocytes - Abdel‐Ghani, Mohammed A. (Reprod Med Biol, 2010)
PURPOSE: To investigate the ability of medium conditioned with bovine cumulus–oocyte complexes (COCs) to support nuclear maturation of canine oocytes recovered from domestic dog ovaries. METHODS: Cumulus–oocyte complexes were obtained from ovaries of domestic bitches (8 months old to 7 years old), and in‐vitro maturation was evaluated in TCM‐199 supplemented with different concentrations (0, 20, 30 or 50%) of bovine COCs‐conditioned medium (BCM). The canine COCs were cultured for 72 or 96 h at 38.5°C in 5% CO(2), 5% O(2) and 90% N(2). The bovine COCs‐conditioned medium was obtained from culture of bovine COCs with TCM‐199 supplemented with 5% FCS for 22 h at 38.5°C in 2% CO(2), 98% air. RESULTS: The proportion of germinal vesicle breakdown (GVBD) after 72 h was significantly higher (P < 0.05) in medium supplemented with 30% BCM (20.7%) compared with the control group (13.4%). The rates of GVBD‐MII stage were significantly higher (P < 0.05) when oocytes were matured with BCM at concentration of 30% (41.5%) compared with control (26.6%) after 72 h in‐vitro culture. After 96 h in‐vitro culture, the oocytes matured in medium supplemented with 30% BCM (5.5%) showed a significant increase (P < 0.05) in the proportion of MII compared with control (0.7%). However, increasing the cultivation time from 72 to 96 h resulted in an increase in oocyte degeneration rate. CONCLUSIONS: The results suggested that bovine COCs‐conditioned medium supplementation significantly increased nuclear maturation of canine oocytes.